The Role of Parents in Preventing Children's Gadget Game Addiction Through Child-Friendly Sports - Kustanti, Dewi; Nurlinah, Nurlinah (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2024)
Gadget addiction in children is a growing concern in the digital age, negatively impacting their physical, social, emotional, and academic development. Parents play a vital role in preventing this addiction by understanding their children's developmental needs and guiding them toward healthier activities. Engaging children in sports can effectively reduce gadget dependency, as studies indicate that excessive screen time decreases physical activity. Parental involvement is essential, particularly as mothers often take a more active role in their children's lives. This study utilizes parental guidance and a literature review to explore the importance of parental education in promoting balanced gadget use. Ultimately, the findings highlight that parents are crucial in shaping their children's personalities and fostering positive habits for healthy development. Contribution: The findings underscore the necessity for targeted interventions that empower parents, particularly mothers, to take an active role in shaping their children's behaviors and promoting a balanced lifestyle in an increasingly digital world.